Screening assessment of cyanobacterial embryotoxicity to Japanese medaka, Oryzias latipes (Actinopterygii: Beloniformes: Adrianichthyidae) - Z. Adámek; J. Sikora; L. Bláha; B. Maršálek (Acta Ichthyologica et Piscatoria, 2011)
Background. Fish embryos and larvae are frequently subject to chronic- and damaging exposure of cyanotoxins released by live and decomposing cyanobacteria Whereas the majority of former studies dealt with the embryotoxicological effects of pure toxins and extracts, we focused on the evaluation of toxic effects of crude cyanobacterial biomass in our study. Materials and methods. Samples of crude cyanobacterial biomass—intended for embryotoxicological tests with eggs of Japanese medaka, Oryzias latipes (strain Q2d-rR.YHNI)—were collected from natural bodies of water in the Czech Republic. Those samples consisted predominantly of: Microcystis aeruginosa, M. flos-aquae, Woronichinia naegeliana, Anabaena sigmoidea, and Aphanizomenon flos-aquae. In the preliminary optimization experiments, various numbers of fertilized medaka eggs (from 1 to 6 per one 10-mL well on a six well polypropylene plate) were hatched under standard conditions. Because of the highest hatching rates, 4 eggs per 10 mL well were selected as an optimal treatment. The embryotoxicological tests were performed according to the OECD 212 guideline in two concentrations (extracts of crude cyanobacterial biomass: 40 and 200 mg · L–1dry weight). Fertilized eggs in stage 6 to 8 (some 2–3 h after fertilization) were introduced into test wells, and hatching performance, duration of embryonic development as well as lethal and sublethal effects were monitored. Results. The hatching rates (treatment with 4 eggs per 10 mL well), achieved in the majority of experimental treatments with cyanobacterial biomass, were significantly different from the control group. Also hatching onset was considerably delayed due the presence of cyanobacterial biomass. The embryotoxicological impacts were more pronounced in higher concentrations of cyanobacterial biomass (200 mg · L–1) compared to lower concentrations (40 mg · L–1). Whilst deformities were not recorded in the control, their highest incidence amounted to 11.8% and 40.9% in 40 and 200 mg · L–1 of cyanobacterial biomass, respectively. Conclusion. Cyanotoxicity significantly affected examined parameters (hatching rates, duration of embryonic development, and morphological deformities occurrence) in medaka embryos. The study proved significant embryotoxic effects upon Japanese medaka at environmentally relevant levels of cyanobacteria commonly occurring in surface waters in Europe.